2011
DOI: 10.1210/me.2010-0294
|View full text |Cite
|
Sign up to set email alerts
|

SGK3 Is an Estrogen-Inducible Kinase Promoting Estrogen-Mediated Survival of Breast Cancer Cells

Abstract: Serum- and glucocorticoid-inducible kinase 3 (SGK3) is a protein kinase of the AGC family of protein kinase A, protein kinase G, and protein kinase C and functions downstream of phosphatidylinositol 3-kinase (PI3K). Recent study revealed that SGK3 plays a pivotal role in Akt/protein kinase B independent signaling downstream of oncogenic PI3KCA mutations in breast cancer. Here we report that SGK3 is an estrogen receptor (ER) transcriptional target and promotes estrogen-mediated cell survival of ER-positive brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 43 publications
3
58
1
Order By: Relevance
“…Most recently, Bago et al reported that SGK3 counteracts the inhibition of PI3K/Akt signaling and stimulates tumor growth (12). SGK3 is amplified and hyperactivated in breast cancer (13), and its expression is regulated by ERα and positively correlates with ERα levels in breast tumors (14,15). Here, we report a mechanism with which SGK3 sustains ERα signaling and drives acquired AI resistance by maintaining EnR homeostasis through preserving SERCA2b function in breast cancer.…”
mentioning
confidence: 56%
See 3 more Smart Citations
“…Most recently, Bago et al reported that SGK3 counteracts the inhibition of PI3K/Akt signaling and stimulates tumor growth (12). SGK3 is amplified and hyperactivated in breast cancer (13), and its expression is regulated by ERα and positively correlates with ERα levels in breast tumors (14,15). Here, we report a mechanism with which SGK3 sustains ERα signaling and drives acquired AI resistance by maintaining EnR homeostasis through preserving SERCA2b function in breast cancer.…”
mentioning
confidence: 56%
“…After AI exposure, most estrogen-dependent cancer cells stop proliferation and go through apoptosis and/or autophagy, but some cancer cells gain estrogen hypersensitivity by ERα mutations or the cross-talk of ERα with growth factor signaling pathways, so that cancer cells can survive and proliferate at low levels of estrogen. Previously, we and others have reported that SGK3 is an ERα direct target, and SGK3 levels positively correlate with ERα levels in breast tumors (14,15). SGK3 can enhance ERα transactivation through phosphorylation of coactivator Flightless-I (25).…”
Section: Sgk3 Retains Erα Expression By Protecting Against Enr Stress-mentioning
confidence: 95%
See 2 more Smart Citations
“…SGK3 is amplified and acts as an oncogene in hepatocellular carcinoma (6). Several studies, including our own, have shown that SGK3 is up-regulated in breast cancer, especially in estrogen receptor (ER)-positive breast cancer (7)(8)(9)(10), and promotes estrogen-mediated cell survival (8,11). Furthermore, Slagsvold et al (12) reported that SGK3 attenuates the degradation of chemokine receptor CXCR4 and promotes breast cancer metastasis.…”
mentioning
confidence: 93%